FRI0398 COMPARISON OF THE EFFICACY AND SAFETY OF TWO HYALURONIC ACIDS IN THE TREATMENT OF KNEE OSTEOARTHRITIS. (2nd June 2020) - Cortet, B.; Lombion, S.; Bruyere, O.
Abstract : Background: Several viscosupplement treatments are available to patients suffering from osteoarthritis (OA) but few comparative clinical trials have been conducted. Objectives: The primary objective of the study was to demonstrate at 24 weeks the non-inferiority of on hyaluronic acid over a second one in terms of efficacy (pain relief) in knee OA patients (Kellgren and Lawrence radiologic stage II or III) with whom oral treatment had failed. Methods: This was a prospective, multicenter, comparative, randomized, double-blinded study (one independent physician evaluator–one physician injector), comparing two viscosupplements: one containing a solution of hyaluronic acid (SYNOLIS VA® 80mg hyaluronic acid and 160 mg sorbitol – Group HA1) and the other containing one of Hylan (SYNVISC ONE ® 48 mg Hylane GF-20 – Group HA2) over a period of 24 weeks. At inclusion, the average VAS Pain (1-100) was 62.5. The patients were randomized in 2 parallel groups at D0 and followed until D168. They received an injection of either HA1 or HA2. Efficacy was primarily assessed using the WOMAC Pain index (daily assessed by the patient during seven days following the injection, and then at D14). During the follow up visits (D28-D84-D168) WOMAC pain, stiffness and function scores were assessed as secondary objectives. At D168, efficacy and satisfaction were also evaluated by the evaluator and by the patient using Likert scale (7 points). Moreover, the number of responders strict each group was evaluated according to the OMERACT-OARSI criteria. According to methodology guidelines, the per protocol (PP) population has been used as primary analysis. The PP population included all patients from the intention to treat (ITT) population who completed the study without any major protocol violation. Results: 202 patients were randomized (ITT population, 96 in the HA1 group and 106 in the HA2 group). Baseline demographic data for the PP population at the time of randomization by treatment group. Patients were predominantly female (66%). The median age of the whole population was 65 years and the median body mass index of 27.4 kg/m 2 . No statistically significant differences between the two treatment groups were observed for any demographic criteria. At D168, 197 presented no protocol violations (94 in the HA1 group and 103 in the HA2 group). This population had a decrease on the overall score of the WOMAC Pain at -29.2+/- 24.1 (SD) in the HA1 group and -31.6 +/-25.5 (SD) in the HA2 group confirming the non-inferiority (P = 0.57 for the difference between groups). Regarding the secondary endpoints, no significant difference has been observed at D14, D28, D84, D168, in the PP population for all the outcome except stiffness at D28. There was also no difference between the responders rate in two groups (79 % for HA1 and 77% for HA2). In terms of safety, both products were well tolerated. No case of allergy or infection in the course of the injection was reported. Serious adverse events have been reported by 4 patients in HA1 group and 3 in HA2 group. Conclusion: In this study, we confirmed the non-inferiority of HA1 compared with HA2 in terms of both efficacy and safety. Disclosure of Interests: Bernard Cortet Consultant of: Aptissen, Sandrine Lombion Consultant of: Aptissen, Olivier Bruyere Consultant of: Aptissen